DEVELOPMENT AND OPTIMIZATION OF TERIFLUNOMIDE-LOADED CHONDROITIN SULPHATE-COATED NANOSTRUCTURED LIPID CARRIERS (NLCs) THROUGH BOX BEHNKEN DESIGN - Campos, Cristobal; Torres-Vergara, Pablo; Godoy, Ricardo; Riquelme, Cristina; Arellano, Noemí; Chavez-Santoscoy, Rocío; Herbas-Goitía, Isabel; Gómez-Gaete, Carolina (Journal of the Chilean Chemical Society, 2023)
Rheumatoid arthritis (RA) is an autoimmune chronic disease characterized by disabling pain and deformity of the joints. Teriflunomide (TFM), a metabolite from leflunomide, is given orally to RA patients, but its gastrointestinal and systemic side effects are severe and not well tolerated. This study aims to optimize and develop nanostructured lipid carriers (NLC) loaded with teriflunomide (NLC-TFM). NLCs were developed by homogenization and ultrasound. The optimization parameters were achieved through a Box-Behnken experimental design. The optimized NLC-TFM were also coated with chondroitin sulfate (NLC-TFM-CHS) to enhance its interaction with target tissues and shift its focus to intra-articular administration. Both formulations were characterized in their morphology, particle size (PS), Zeta potential, entrapment efficiency (EE%), drug loading (DL%), molecular interactions and in vitro release kinetics. The developed NLC-TFM and NLC-TFM-CHS exhibited a spherical morphology, Zeta potential lower than -30 mV, mean PS of 178.6-211 nm, EE% of 85.95-65.78 % and DL% of 3.97-2.97%, respectively. Thermal and crystalline behavior analyses suggested that TFM is dissolved within the lipidic matrix. The release of TFM showed a biphasic pattern, with an initial burst release followed by a sustained release, being the latter more marked in NLC-TFM-CHS. The developed formulations show promise as delivery systems for targeted therapy of RA through intra-articular administration.